THE ROLE OF ENTREPRENEURIAL ORIENTATION ON THE PERFORMANCE OF FOOD AND BEVERAGE SMEs - Dwitama, Michael; Puspitowati, Ida (Graduate Program of Universitas Tarumanagara, 2025)
Through an empirical analysis, this study aims to determine how innovation (IN), proactiveness (PR) and risk-taking (RT) affect the Small and Medium Enterprises performance (SMEs Perf) venture in West Jakarta's food and beverage sector. Based on the theory of Resource Based Vied (RBV) philosophy, this study examines how organizational resources and capabilities relate to performance results. That 66 SMEs owners were surveyed online using Google Forms, and the data is gathered by using a non-probability technique, and using purposive sampling approach. SmartPLS version 4.1.0.5 software and structural equation modeling (SEM) were used for data analysis. IN has a major influence on SMEs Perf, according to the findings, whereas PR and RT have favorable but statistically minor effects on the SMEs Perf of food and beverage in West Jakarta.